The Finite Element Analysis of Auxiliary Transformer Clamp Mechanic Strength for the HXD1B High Power Locomotive - HUANG Xi-you; CHEN Xiang-ling; LIAO Bao-hua (机车电传动)
With finite element analysis by the ANSYS software, the mechanic strength was analyzed and calculated when the auxiliary transformer clamping piece was brought to bear three direction impact of vertical 3g transverse 3g and longitudinal 5g peak acceleration, which indicated the max stress of all working conditions was less than material permitted. The reliability of clamp mechanic strength was verified by experiment too.